Study Of Axial Length In Retinal Vein Occlusions - Dr BK Vinod kumar , Dr Swetha, Dr CH Srinivasa Murty, (International Journal of Scientific Research and Management (IJSRM), 2015)
Retinal vein occlusion is the most common retinal occlusive disorder encountered by ophthalmologists and is usually associated with a variable amount of visual loss.RVO most commonly affects the venous blood supply of the entire retina, central retinal vein occlusion (CRVO) or a quadrant by one of the branches, Branch retinal vein occlusion (BRVO). Less commonly the superior or inferior half of the retina alone is affected, Hemi retinal vein occlusion.